Learnable Programming: Blocks and Beyond. - BAU, DAVID; GRAY, JEFF; KELLEHER, CAITLIN; SHELDON, JOSH; TURBAK, FRANKLYN (Communications of the ACM, 2017)
The article discusses the use of blocks-based programming as a form of learnable programming. Topics include the role of blocks-based programming in chunking computational patterns and reducing the cognitive load of learners, the use of abstractions to make coding more learnable, and the possibility of combining text-based and blocks-based programming for greater efficiency.